DEHUMANISASI DAN HUMANISASI DALAM NYANYIAN ANGSA KARYA W.S. RENDRA - Insum Malawat (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Nyanyian Angsa by W.S. Rendra is an example of humanist literature that tells about dehumanization in the country. Nyanyian Angsa is one of Rendra's best works from a number of human-themed works. The appearance of the profession of priests, doctors, procures representing the ruling group, superiors with subordinates, congregations, patients, and prostitutes (Maria Zaitun) as objects or ordinate is only an example that humanity problems commonly experienced by common people. This paper aims to illustrate the humanitarian problem (dehumanization) contained in the Nyanyian Angsa and express humanization thinking as a preventive measure.Reference theory is humanism and hermeneutics. Dehumanization in Nyanyian Angsa is represented by injustice, tolerance, disrespect and appreciate, and have not compassion. In general, the value of humanization to be conveyed through this poem is to be able to humanize others, first, we should be able to humanize ourselves. Another value is the materialistic orientation of life that can enrich dehumanization and weaken or even drown human values (humanization).